2013
DOI: 10.3329/bvet.v30i1.16281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics on haematology and biochemical parameters in mice

Abstract: Probiotic organisms are live microorganisms thought to be beneficial to the host. To know the effect of probiotic supplemented food on haemato-biochemical parameters in mice, a total of 20 two-month-old Swiss Albino mice were randomly divided into four equal groups. Group A was control, fed commercial mouse pellets, and others were treated with 5 g (group B), 10 g (group C) and 20 g (group D) probiotics (curd), respectively, in mouse pellets for 45 days. Total erythrocyte count and haemoglobin concentration we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
4
6
1
5
Order By: Relevance
“…Because the initial levels exceeded the common physiological range (150-190 g/L), it is difficult to make a conclusion as to the real direction of chlorophyll effects. In addition, 7 dogs of the LF group had increased haemoglobin levels 14 days after application of L. fermentum CCM 7421, and a similar dose-dependent effect in mice has been reported (Salahuddin 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Because the initial levels exceeded the common physiological range (150-190 g/L), it is difficult to make a conclusion as to the real direction of chlorophyll effects. In addition, 7 dogs of the LF group had increased haemoglobin levels 14 days after application of L. fermentum CCM 7421, and a similar dose-dependent effect in mice has been reported (Salahuddin 2013).…”
Section: Discussionmentioning
confidence: 61%
“…Penelitian oleh Astawan et al (2011), pada kelompok tikus yang diinfeksi Enteropathogensis E. coli (EPEC) menunjukan bahwa kelompok tikus yang diberi diet probiotik memiliki jumlah sel darah merah yang lebih tinggi dibandingkan dengan kelompok tikus yang hanya diberi diet standar. Sementara pada penelitian Salahuddin et al (2013), menunjukan bahwa terjadi perubahan yang signifikan pada parameter sel darah merah yaitu peningkatan jumlah eritrosit dan konsentrasi hemoglobin pada kelompok tikus yang diberikan diet probiotik dibandingkan dengan kelompok yang tidak mendapat diet probiotik. 6,14 Sebagian besar penelitian tentang pengaruh probiotik berfokus pada pencegahan dan terapi penyakit gastrointestinal, padahal probiotik memiliki potensi dalam mencegah perluasan infeksi dan berpengaruh pada konsentrasi hemoglobin.…”
Section: Pendahuluanunclassified
“…Sementara pada penelitian Salahuddin et al (2013), menunjukan bahwa terjadi perubahan yang signifikan pada parameter sel darah merah yaitu peningkatan jumlah eritrosit dan konsentrasi hemoglobin pada kelompok tikus yang diberikan diet probiotik dibandingkan dengan kelompok yang tidak mendapat diet probiotik. 6,14 Sebagian besar penelitian tentang pengaruh probiotik berfokus pada pencegahan dan terapi penyakit gastrointestinal, padahal probiotik memiliki potensi dalam mencegah perluasan infeksi dan berpengaruh pada konsentrasi hemoglobin. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pengaruh probiotik (Lactobacillus spp.)…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kinal et al (2007) suggested that yeast cells also improved the digestibility and absorption of minerals such as phosphorus, magnesium, calcium, copper, potassium, zinc, and manganese. Study about the effect of probiotic on hematology was reported in mice and result showed that probiotic increased hematological parameters and lipid profile (Salahudin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%